Economic and energy consumption analysis of smart building – MEGA house. (1st May 2016) - Cheng, Min-Yuan; Chiu, Kuan-Chang; Lien, Li-Chuan; Wu, Yu-Wei; Lin, Jing-Jhe
Abstract: Energy efficiency and carbon reduction of new buildings are key objectives of policies that aim to decrease electric use nationwide, particularly during the summer, when electricity usage is at its highest. A case study was developed to test the energy-conservation performance and economic feasibility of the creative and intelligent open building "MEGA House". MEGA House focuses on making improvements in four key areas: (a) Material, (b) Electronic, (c) Green Building, and (d) Automation. This paper focuses on applications in the areas of Electronic and Green Building. The economic analysis in this paper of electricity consumption and of the potential energy-savings is based on the use of energy conservation equipment such as earth tubes and solar chimneys, situation simulations, field measurements at four experimental stages, and economic calculations. According to the results of measurement and economic analysis, the MEGA House demonstrated optimal energy conservation performance. Using an earth tube (fan) and a solar chimney (exhaust fans) in the MEGA House lowered the indoor temperature about 1∼2 °C in summer, while using an earth tube (fan) instead of an electric heater increased the indoor temperature as much as 3–4 °C. In terms of economic benefits, the using the energy-conservation facilities installed in MEGA House reduced electricity expenditures by NT$8537.76 and decreased CO2 emissions by around 1288.83 kg per year. Graphical abstract: Highlights: MEGA House makes improvements in material, electronic, green, and automation. Analyze power consuming and CO2 emission based on the use of energy-saving devices. The financial cost of CO2 emissions and of electricity is evaluated. The MEGA House demonstrates optimal energy conservation performance.